PROFESSIONAL TRAINING THROUGH THE DEVELOPMENT OF STUDENTS' LEARNING AND COGNITIVE COMPETENCE IN THE PROCESS OF HIGHER EDUCATION - Rakhimov Zokir Toshtemirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. The article discusses the importance of improving the quality of higher education, the rapid development of science, technology and engineering, the formation of important professional qualities through the development of students' educational and cognitive competencies in higher education, speed, effective adaptation to rapid changes in a short period of time, the development of students' self-awareness and creative abilities in the development of professional training, the importance of ensuring constitutional human rights to education, the importance of studying and learning on the basis of professional training, collective and individual research, mastering experiences, additional mastering, self-education, achieving the goal and organizing one's own success, explaining one's own goal, planning, analyzing, reflecting on educational and cognitive activities, organizing self-assessment, asking questions about the evidence to be verified, searching for the causes of phenomena, showing understanding or misunderstandings in solving the problem under study, working with instructions. issues are interpreted.